Suicidal Ideation Is Associated With Reduced Functional Connectivity and White Matter Integrity in Drug-Naïve Patients With Major Depression - Reis, Joana Vanessa; Vieira, Rita; Portugal-Nunes, Carlos; Coelho, Ana; Magalhães, Ricardo; Moreira, Pedro; Ferreira, Sónia; Picó-Pérez, Maria; Sousa, Nuno; Dias, Nuno; Bessa, João M. (Frontiers in Psychiatry, 2022)
Depression is a highly prevalent psychiatric disorder affecting millions of people worldwide. Due to the challenges imposed by the COVID-19 pandemic, the prevalence of this disorder is thought to have increased even more. Depression is characterized by decreased mood or loss of interest in daily activities, changes in feeding and circadian rhythms and significant impairments in cognitive and executive function. In addition, the occurrence of recurrent thoughts of death and suicidal ideation confers depressed patients a higher risk of suicide than the general population. This study aimed to explore neuronal correlates of suicidal ideation in 25 drug-naïve depressed patients using two-different magnetic resonance imaging (MRI) modalities, resting state functional MRI (fMRI) and diffusion tensor imaging (DTI). Resting state allowed the exploration of connectivity patterns in the absence of a specific stimulus and DTI allowed a detailed analysis of structural white matter integrity with measures like fractional anisotropy (FA). Probabilistic independent component analysis (PICA), network-based statistics and tract-based spatial statistics (TBSS) were applied to analyze resting-state fMRI and DTI data, respectively. Our results showed that in our sample of drug-naïve depressed patients, suicidal ideation was negatively correlated with resting-state functional connectivity rsFC in the visual networks and with FA in the genu of corpus callosum and in the right anterior corona radiata. In addition, a significant association was identified between suicidal ideation and a functional connectivity network that included connections between regions in the superior and orbitofrontal cortex, the cerebellum, the cingulate gyrus as well as temporal and occipital regions. Importantly, these results were found to be specific to suicidal ideation and were not mediated by the disease severity. In conclusion, this work has expanded our knowledge about the possible functional and structural neuronal correlates of suicidal ideation in drug-naïve patients with depression, paving the way for future personalized therapeutic approaches.